Art geeks and prom queens - Noel, Alyson (New York : St. Martin's Griffin, 2005)
Seventeen-year-old Alex struggles to fit in at her new private school in Southern California until she meets the very popular Kristi; however, the deeper she becomes immersed in her new crowd, the more she realizes Kristi is not to be messed with.
Young Adult
Young Adult
School Library Journal
Booklist
950
Keywords: Interpersonal relations -- Fiction; Friendship -- Fiction; High schools -- Fiction; Schools -- Fiction; Los Angeles (Calif.) -- Fiction; Interpersonal relations -- Fiction; Friendship -- Fiction; High schools -- Fiction; School stories